Intrathecal Morphine and Pulmonary Complications after Arthroplasty in Patients with Obstructive Sleep Apnea: A Retrospective Cohort Study. (April 2020) - Bai, Johnny W.; Singh, Mandeep; Short, Anthony; Bozak, Didem; Chung, Frances; Chan, Vincent W. S.; Bhatia, Anuj; Perlas, Anahi
Abstract : Background: Intrathecal morphine is commonly and effectively used for analgesia after joint arthroplasty, but has been associated with delayed respiratory depression. Patients with obstructive sleep apnea may be at higher risk of postoperative pulmonary complications. However, data is limited regarding the safety of intrathecal morphine in this population undergoing arthroplasty. Methods: This retrospective cohort study aimed to determine the safety of intrathecal morphine in 1, 326 patients with documented or suspected obstructive sleep apnea undergoing hip or knee arthroplasty. Chart review was performed to determine clinical characteristics, perioperative events, and postoperative outcomes. All patients received neuraxial anesthesia with low-dose (100 μg) intrathecal morphine (exposure) or without opioids (control). The primary outcome was any postoperative pulmonary complication including: (1) respiratory depression requiring naloxone; (2) pneumonia; (3) acute respiratory event requiring consultation with the critical care response team; (4) respiratory failure requiring intubation/mechanical ventilation; (5) unplanned admission to the intensive care unit for respiratory support; and (6) death from a respiratory cause. The authors hypothesized that intrathecal morphine would be associated with increased postoperative complications. Results: In 1, 326 patients, 1, 042 (78.6%) received intrathecal morphine. The mean age of patients was 65 ± 9 yr and body mass index was 34.7 ± 7.0 kg/m 2 . Of 1, 326 patients, 622 (46.9%) had suspected obstructive sleep apnea (Snoring, Tired, Observed, Pressure, Body Mass Index, Age, Neck size, Gender [STOP-Bang] score greater than 3), while 704 of 1, 326 (53.1%) had documented polysomnographic diagnosis. Postoperatively, 20 of 1, 322 (1.5%) patients experienced pulmonary complications, including 14 of 1, 039 (1.3%) in the exposed and 6 of 283 (2.1%) in the control group ( P = 0.345). Overall, there were 6 of 1 322 (0.5%) cases of respiratory depression, 18 of 1, 322 (1.4%) respiratory events requiring critical care team consultation, and 4 of 1, 322 (0.3%) unplanned intensive care unit admissions; these rates were similar between both groups. After adjustment for confounding, intrathecal morphine was not significantly associated with postoperative pulmonary complication (adjusted odds ratio, 0.60 [95% CI, 0.24 to 1.67]; P = 0.308). Conclusions: Low-dose intrathecal morphine, in conjunction with multimodal analgesia, was not reliably associated with postoperative pulmonary complications in patients with obstructive sleep apnea undergoing joint arthroplasty. Abstract : Low-dose intrathecal morphine, in conjunction with multimodal analgesia, was not associated with increased risk of postoperative pulmonary complications in patients with obstructive sleep apnea.